2017
DOI: 10.1007/s10433-017-0428-1
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional social support is associated with healthcare utilization among older Mexican adults

Abstract: In this study, we aimed to estimate the association between social support and healthcare utilization among older Mexican adults. We conducted a prospective study with 4027 older adults aged 65-74 in rural areas in seven Mexican states. Data were collected at baseline (2007) and 14 months later (2009). Healthcare utilization was defined as number of visits to a physician for preventive or curative purposes in the last 6 months. Multidimensional social support was operationalized into two components: structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
2
12
1
Order By: Relevance
“…Participants reporting more access to informal social support had higher health care utilization rates. Previous studies have proposed social support as an enabling factor providing a strong linkage between the need for health care and the actual utilization of the available health services (Litwin, 1997; Salinas-Rodriguez et al, 2018), particularly among older adults who may present with comorbidities and other physical disabilities, and with limited socioeconomic resources. The findings of this study provide some evidence to support these findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants reporting more access to informal social support had higher health care utilization rates. Previous studies have proposed social support as an enabling factor providing a strong linkage between the need for health care and the actual utilization of the available health services (Litwin, 1997; Salinas-Rodriguez et al, 2018), particularly among older adults who may present with comorbidities and other physical disabilities, and with limited socioeconomic resources. The findings of this study provide some evidence to support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Maulik, Eaton, and Bradshaw (2010) further reported that increased social support decreased the odds of using mental health services and speciality care by 60% and 40% to 50%, respectively. Other studies found that greater social support significantly relates to health care use among older persons (e.g., Melchiorre et al, 2013; Salinas-Rodriguez et al, 2018). However, these diverse observations may not reflect the situation in Ghana due to sociocultural and demographic peculiarities (Gyasi, Buor, et al, 2018).…”
Section: Informal Social Support Health and Health Carementioning
confidence: 95%
See 1 more Smart Citation
“…In contrast to primary care where services are typically provided within fixed-length appointment slots, specialists’ appointment lengths are highly variable and diagnosis-dependent, which may result in variable waiting times and inconvenience to patients [38]. Strong social support has also been shown to increase the probability of physician visits [39]. Although the level of social support among public rental housing residents was not assessed in this study, the lack of social support among public rental housing residents may potentially reduce their adherence to specialist outpatient clinic visits, especially among patients with ambulatory problems and should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, since 2009 Mexico has a non-contributory pension program (formerly known as 70 y más−70 and over, and now as the Programa para el Bienestar de los Adultos Mayores -Program for the Welfare of Older Adults) which consists of the bimonthly payment of 2,750 Mexican pesos (115 US dollars approx. ), and is intended to be universal to all individuals 68 years of age or older (11,12).…”
Section: Introductionmentioning
confidence: 99%